2020
DOI: 10.14254/2071-789x.2020/13-4/15
|View full text |Cite
|
Sign up to set email alerts
|

Gender question: Econometric answer

Abstract: There has been an increased interest in the studies on female entrepreneurship due to the changing sociocultural conditions at the global markets. Despite this trend, there is still a lack of understanding about the female entrepreneurs' role in the internationalization processes of firms and states. The purpose of this research is to examine the impact of gender differences globally. The critical review of available literature and international reports on the topic revealed the research gap in the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Therefore, it can be concluded that the implementation of a business leads to an objective awareness of the need for personal development and improvement/professionalization. This fully correlates with previous studies [66][67][68].…”
Section: Resultssupporting
confidence: 93%
“…Therefore, it can be concluded that the implementation of a business leads to an objective awareness of the need for personal development and improvement/professionalization. This fully correlates with previous studies [66][67][68].…”
Section: Resultssupporting
confidence: 93%
“…In addition, political decision makers and a nationwide educational policy (supporting the introduction of entrepreneurial studies, increasing the number of science subjects, and orienting girls to towards IT and technical subjects) play an important role along with business support programmes that help enterprises; and they will be responsible for changing the persisting male stereotype of what is a successful entrepreneur (Eddleston et al, 2016). Governments should be interested in formulating policies that encourage women to take a more active part in economic life Stavytskyy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to Stavytskyy et al on the issue of gender gap and its mitigation (mainly the Global Gender Gap Index) is influenced not only by economic factors, e.g., an increase in GDP per capita, a decrease in unemployment, etc. (Stavytskyy et al, 2020). Within the analyses of GDP and well-being, the Portuguese GDP alone hardly has any impact on the well-being index.…”
Section: Literature Reviewmentioning
confidence: 94%